12m+5n-3m+10n=

Simple and best practice solution for 12m+5n-3m+10n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12m+5n-3m+10n= equation:


Simplifying
12m + 5n + -3m + 10n = 0

Reorder the terms:
12m + -3m + 5n + 10n = 0

Combine like terms: 12m + -3m = 9m
9m + 5n + 10n = 0

Combine like terms: 5n + 10n = 15n
9m + 15n = 0

Solving
9m + 15n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-15n' to each side of the equation.
9m + 15n + -15n = 0 + -15n

Combine like terms: 15n + -15n = 0
9m + 0 = 0 + -15n
9m = 0 + -15n
Remove the zero:
9m = -15n

Divide each side by '9'.
m = -1.666666667n

Simplifying
m = -1.666666667n

See similar equations:

| 160+.15m=241 | | 7x+117=-6x | | log[2]3x-6=4 | | -6x-3=3-6y | | 7x-35+3=6x-42 | | (x-6)-7=-3 | | 12p+19q+p-6q-3p= | | 1+x+2=3+x+4 | | 4(x+2)=30+3x | | X^2lnx-4lnx=0 | | 6a=80-4d | | 8x+10=8x-9 | | X^2=220+5 | | x^2+5x-3=3x+5 | | x^2+16x-15=0 | | 17=(-13)-(8x) | | 21-15=3(x-7) | | 15a+14b+6c+5c-5b-5a= | | 2x+7y+z=29 | | 4x-2(x-3)=-2+5x-4 | | 6x-3x=7 | | 50=47+12+4w | | -5(x)+23=-7 | | 3x+2y+z=17 | | 6r+2(r+6)=4r+12 | | 12+4x=-2x-9 | | 3y+8x+3=14+8x | | x^2-6x+4=-9x+2 | | 3=0.5+11 | | 2x+5+110= | | 2x+4=2x+2(x+2) | | x^2-8x-5=4 |

Equations solver categories